2014
DOI: 10.1002/gj.2583
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and significance of Cu–Zn intermetallic compounds in the Jingxi gold deposit, western Tianshan Mountains, NW China

Abstract: A group of Cu-Zn intermetallic compounds has been discovered in breccias at the Jingxi gold deposit, NW China. The host rocks, silicified tuff and andesite, are cut by pyrite-bearing quartz veins and are intensely silicified which leads to a high SiO 2 content (over 85%). The main component of breccia is siliceous rock, with the cement mainly siliceous and tuffaceous. Under the reflected light microscope, the Cu-Zn intermetallic compounds have quadrilateral shapes which range in size from 6 to 28 μm. Scratches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Liu et al . () report an excellent case study of the Jingxi gold deposit in Xianjiang, which originally formed in the Early Carboniferous and was then reworked in the Early Triassic. They discovered a group of Cu–Zn intermetallic compounds, containing minor Sn and trace Ni, and concluded that these Cu–Zn intermetallic compounds were formed under conditions of low f O 2 and f S 2 values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al . () report an excellent case study of the Jingxi gold deposit in Xianjiang, which originally formed in the Early Carboniferous and was then reworked in the Early Triassic. They discovered a group of Cu–Zn intermetallic compounds, containing minor Sn and trace Ni, and concluded that these Cu–Zn intermetallic compounds were formed under conditions of low f O 2 and f S 2 values.…”
mentioning
confidence: 99%
“…Formations and preservations of these deposits are openly debated, due to the fact that investigation of the geological characteristics, mineral compositions, and mineralization styles is very poorly known . Liu et al (2014) report an excellent case study of the Jingxi gold deposit in Xianjiang, which originally formed in the Early Carboniferous and was then reworked in the Early Triassic. They discovered a group of Cu-Zn intermetallic compounds, containing minor Sn and trace Ni, and concluded that these Cu-Zn intermetallic compounds were formed under conditions of low fO 2 and fS 2 values.…”
mentioning
confidence: 99%